Trapped in Lifestyle? How Financial Literacy and Millennial Investor’s Psychology Determine Investment Decisions in Indonesia - Abdullah, Abdullah; Rachma, Nur; Rahman, Karlina Ghazalah; Reynilda, Reynilda (Integrated Journal of Business and Economics (IJBE), 2025)
Studying the impact of financial literacy, lifestyle, consumerism, and psychology on Indonesian millennial investors' investment decisions is the goal of this study. 205 respondents between the ages of 17 and 30 who were dispersed over 10 capital market research communities in Indonesia were selected by purposive sampling. The findings demonstrate the strong direct influence of investor psychology, lifestyle, and financial literacy on investment decisions. Decisions about investments are not impacted by consumption. There is no discernible relationship between investor psychology and financial literacy. Consumer behavior and lifestyle have a big impact on investor psychology. Decisions about investments are influenced by investor psychology. Investment decisions are not impacted by financial literacy through investor psychology. Investment decisions are impacted by lifestyle through investor psychology. Investment decisions are significantly impacted by consumptive behavior through investor psychology. The study suggests that financial service providers and investment platforms should tailor their products and communication strategies to align with the psychological and lifestyle traits of millennial investors, rather than relying solely on traditional financial education.